Association between restless legs syndrome and sleep quality in Peruvian medical students - Rubí Paredes-Angeles; Cesar Copaja-Corzo; Alvaro Taype-Rondan (PLoS ONE, 2025)
Objective To evaluate the association between restless legs syndrome (RLS) and sleep quality in Peruvian medical students. Methods Cross sectional study with a secondary data analysis. The study included Peruvian medical students surveyed in 2020. The outcome was sleep quality evaluated using the Pittsburgh Sleep Quality Index (PSQI), and the exposure variable was RLS assessed with the International Restless Legs Syndrome Study Group (IRLSSG) scale. To address the research question, we employed Poisson regression models with robust variance. Results We analyzed information from 3139 medical students (61.1% female, median age 22.3 years). 15.3% experienced symptoms of Restless Legs Syndrome (RLS), and 77.2% had poor sleep quality. The prevalence of poor sleep quality was higher in female participants (80.0%) and those with symptoms of anxiety (92.8%), depression (91.6%), and severe nomophobia (86.3%). In the multivariable model, the presence of RLS symptoms was associated with poor sleep quality (prevalence ratio: 1.05, 95% CI 1.01 - 1.09, p < 0.013). Conclusion We found a high prevalence of poor sleep quality, notably associated with RLS. Other factors associated with poor sleep quality were the academic year of study, anxiety, depression, and nomophobia.